Diabetes Prevention in Nepal: Assessment of Knowledge and Attitude of the 40+ Patients - Sharma, Saraswati (Journal of Advanced Academic Research, 2015)
Introduction: Diabetes was once thought to be a problem exclusively of developed countries and the wealthy. Now diabetes has imposed a heavy burden on both the developed and developing countries. Urbanization, with the adoption of “western lifestyles”, has been identified as the main reason. The objective of this study is to explore demographic details of diabetes patients and assess the knowledge and attitude regarding preventive measures on diabetes mellitus among the people above 40 years old in Nepal. Method: Descriptive cross-sectional study involving 100 people measure was used to carry out this research. Result: About 20.54% of the respondents responded that sedentary life style is the main cause of diabetes, 18.98% pointed out frequent urination as the major symptom. 84% responded that diabetes could be prevented. 19.04 % considered diet control could help in the treatment of diabetes. 100% respondent responded that smoking and drinking alcohol should be avoided while 18.98% took kidney disease and eye problem as the major complications of diabetes. Majority of the respondents (88%) responded that exercise could help in the control and prevention of diabetes. Conclusion: The risk of diabetes continued to increase worldwide due to population growth, aging, urbanization and increasing prevalence of physical inactivity and obesity. Most of the studies have proved that the number will increase more in developing countries due to rapid urbanization, dietary pattern and sedentary life. Journal of Advanced Academic Research Vol.1(1) 2014: 46-52